Calcium intake and risk of fracture: systematic review. (29th September 2015) - Bolland, Mark J; Leung, William; Tai, Vicky; Bastin, Sonja; Gamble, Greg D; Grey, Andrew; Reid, Ian R
Abstract : Objective To examine the evidence underpinning recommendations to increase calcium intake through dietary sources or calcium supplements to prevent fractures. Design Systematic review of randomised controlled trials and observational studies of calcium intake with fracture as an endpoint. Results from trials were pooled with random effects meta-analyses. Data sources Ovid Medline, Embase, PubMed, and references from relevant systematic reviews. Initial searches undertaken in July 2013 and updated in September 2014. Eligibility criteria for selecting studies Randomised controlled trials or cohort studies of dietary calcium, milk or dairy intake, or calcium supplements (with or without vitamin D) with fracture as an outcome and participants aged >50. Results There were only two eligible randomised controlled trials of dietary sources of calcium (n=262), but 50 reports from 44 cohort studies of relations between dietary calcium (n=37), milk (n=14), or dairy intake (n=8) and fracture outcomes. For dietary calcium, most studies reported no association between calcium intake and fracture (14/22 for total, 17/21 for hip, 7/8 for vertebral, and 5/7 for forearm fracture). For milk (25/28) and dairy intake (11/13), most studies also reported no associations. In 26 randomised controlled trials, calcium supplements reduced the risk of total fracture (20 studies, n=58 573; relative risk 0.89, 95% confidence interval 0.81 to 0.96) and vertebral fracture (12 studies, n=48 967. 0.86, 0.74 to 1.00) but not hip (13 studies, n=56 648; 0.95, 0.76 to 1.18) or forearm fracture (eight studies, n=51 775; 0.96, 0.85 to 1.09). Funnel plot inspection and Egger's regression suggested bias toward calcium supplements in the published data. In randomised controlled trials at lowest risk of bias (four studies, n=44 505), there was no effect on risk of fracture at any site. Results were similar for trials of calcium monotherapy and co-administered calcium and vitamin D. Only one trial in frail elderly women in residential care with low dietary calcium intake and vitamin D concentrations showed significant reductions in risk of fracture. Conclusions Dietary calcium intake is not associated with risk of fracture, and there is no clinical trial evidence that increasing calcium intake from dietary sources prevents fractures. Evidence that calcium supplements prevent fractures is weak and inconsistent.